Fine-grained and Coarse-grained Knowledge in Euthydemus 293b7–d1. Issue 2 (3rd April 2019) - Duncombe, Matthew
ABSTRACT: McCabe [2021 : 137–40] identifies a crucial ambiguity in the terms 'learns' and 'knows'. Such terms can be read as either 'perfective' or 'imperfective'. This is an aspect difference. The former indicates a settled state, the latter a directed process. McCabe uses this insight to show how Socrates can rebut the sophists' view of meaning, render compelling Socrates' self-refutation arguments, and explain the Socratic connections between learning, knowledge, and how one should live. In the final section of the Euthydemus, Euthydemus offers the 'Omniscience Sophism', and the related, rather cheeky, 'Father Sophisms'. McCabe [ibid .: 140–2] suggests that the Omniscience Sophism might be addressed by identifying an aspect ambiguity, but does not follow up her point in detail. In this response, I argue that McCabe's instinct is good and that a relative term, such as 'knowledgeable', can be understood as having two senses. That distinction is between what I call 'fine-grained' and 'coarse-grained' senses of 'knowledgeable'. I suggest that this distinction that tracks McCabe's aspect distinction between senses of 'learns' and best explains the fallacy committed in the Omniscience Sophism.